Analisis Pendekatan Pembelajaran Bahasa Indonesia Berbasis Game dalam Kurikulum Merdeka: Sebuah kajian Literatur - Dahlia Purnamasari; Hindun Hindun (Universitas Maritim AMNI Semarang, 2024)
Approach is an effort to achieve a goal and become successful. In the world of education, an approach can be defined as a plan, method, or series of activities aimed at achieving certain educational goals. A learning approach can be defined as a plan that includes a series of activities aimed at achieving certain educational goals. This research aims to find out how effective the game-based Indonesian language learning approach is in the independent curriculum. Background This research begins with the need to understand in depth the use of game-based learning approaches in the Independent Curriculum in Indonesian language subjects. Literature study method Studying previous research through literature study which is used to provide an understanding of previous results, both successes and challenges in implementing a game-based learning approach. This helps in research planning to take advantage of positive experiences and overcome obstacles that may arise.